Profiling Ethiopian migration: a comparison of characteristics of ethiopian migrants to Africa, the middle east and the north - Kuschminder, Katie (2013)
This paper provides an overview of the different characteristics of migrants from Ethiopia to three different migration destinations: (1) northern countries, (2) other African countries, and (3) the Middle East. The paper is based on a recent household survey of 1,286 migrant, non-migrant and return migrant households in Ethiopia. First, the results show that the characteristics of the migrants and their origin households differ depending on migration destination. Secondly, the increased migration flows to Africa and the Middle East in recent decades have played an important role in reshaping the profile of Ethiopian migrants. Furthermore, the results show that current Ethiopian migration flows coincide with some of the current global migration trends but at the same time contrast some of the overall migration figures representing Africa.